ANALISA KEGAGALAN MATERIAL SA-210C PADA APLIKASI BOILER STEAM PIPE - Andi Rinaldi Hasan (Journal of Mechanical Engineering and Mechatronics, 2018)
The purpose of this study was to determine the cause of pipe failure in super saturated area boilers. The research method begins with the collection of chronological data on material failure, operating data collection and material sampling. After material sampling is carried out, photos of failed material are subsequently carried out, thickness measurements, hardness testing, metallographic testing and internal pipe pressure calculations. The results showed that the outside of the pipe had erosion corrosion due to a reduction in thickness of the pipe, especially location 1. Thickening was caused by high pressure auxiliary steam bursts from the sootblower equipment which lasted for a long time at the pipe surface, resulting in Fe + O FeO reaction. FeO formed at the beginning will be released due to high-pressure auxiliary steam bursts and at the same time the auxiliary steam burst reacts chemically again to form FeO. Because of the repeated processes, the pipe thickness slowly decreases. As a result of the depletion, the pipe reaches a critical value so it is unable to withstand the pressure from the pipe and eventually fails. The failure factor, supported by some data on boiler water quality and continuous operating pressure from sootblower that affect erosion corrosion. Changes in microstructure also affect the decrease in hardness in the material which can be seen from the size and shape of the grain.